Moderasi Beragama: Meninjau Hadis-Hadis Hukuman Mati bagi Orang Murtad - Nasirudin Al Ahsani (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2020)
Islam is a religion that gives mercy to all creation, a religion that teaches peace, safety and prosperity. In recent years, there have been many wicked individuals trying to destroy Islam. Unlike in the past where waging war on Islam were done only with swords, today's war against Islam is more powerful, that is by planting seeds of doubt in every Muslim's heart. Both in terms of aqidah (Creed) and Sharia (Islamic law). The current study is a library research. The main sources of this research data were taken from the kutub al sittah (the authentic six): á¹¢aá¸¥Ä«á¸¥ BukhÄrÄ«, á¹¢aá¸¥Ä«á¸¥ Muslim, Sunan AbÄ« DÄwÅ«d, Sunan al-NasÄÊ¾i, Sunan al-Tirmidhi, and Sunan Ibn MÄjah. Meanwhile, the secondary sources were taken from the takhrij and shurÅ«á¸¥ al-hadÄ«th books. The conclusion of the current study reveals that the death penalty for those who turn back from Islam or apostates can be applied if they meet two conditions: 1) Leaving Islam either by word or deed; 2) Committing criminal acts, such as: dividing Muslims, creating chaos, damage, disobeying the state, and helping the enemy in fighting the Muslims. The author concludes that neither the verses in the Qur'an nor the hadiths of the Prophet PBUH immediately order the killing of a person who turns back from Islam, unless that person commits insubordination, is in league with the enemy and other similar things.